Social informatics. 9th International Conference, SocInfo 2017, Oxford, UK, September 13-15, 2017, Proceedings /: 9th International Conference, SocInfo 2017, Oxford, UK, September 13-15, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available